Kajian Learning obstacle pada Materi Peluang untuk Jenjang SMP Ditinjau dari Literasi Matematis PISA 2021 - Fairuz Aulia Shabrina; Encum Sumiaty; Eyus Sudihartinih (Jurnal Pendidikan Matematika : Judika Education, 2022)
The purpose of this study is to find out the type of learning obstacle experienced by students in the opportunity material at the junior level in view of PISA 2021 literacy. The method used in this study is a qualitative method using a didactical design research framework, which focused on the study of learning obstacles. Instruments for studying learning obstacles on the topic of opportunity are designed based on mathematical literacy of PISA 2021. Participants in this study consisted of three 10th grade students at one of the MA (Madrasah Aliyah) in Bandung, one class 11th student at one of the MA in Bandung, two 10th grade students at one of the high schools in Jakarta. Data is collected through tests and interviews through WhatsApp. The results showed that there were four types of learning obstacles experienced by participants, namely students' incomprehension to the concept of opportunities used, students' incompetence to the context of information from the given problem, lack of careful reading and doing, and not used to working on problem solving type problems.